Edukasi Obat High Alert Hipertensi untuk Meningkatkan Pengetahuan Pengobatan di Kelurahan Rempoa Kota Tangerang Selatan - Muhamad Iqbal Saputra; Sirajudin Noor; Fidelma Mariyam; Erlin Enjelina; Aurayacinta Insanda; Widya Kartika Putri (Yayasan Daarul Huda Kruengmane, 2025)
Hypertension is a chronic disease closely associated with the risk of serious cardiovascular complications and shows an increasing prevalence both globally and in Indonesia, particularly in Rempoa Subdistrict, South Tangerang. This study aims to measure the impact of educational counseling regarding the use of high-alert antihypertensive medications on the knowledge level of the surrounding community. The research employed a quantitative experimental approach with a pre-test and post-test design involving 30 hypertensive participants selected purposively. The counseling was delivered through presentation media and educational leaflets, accompanied by interactive discussions on dosage, timing of consumption, and side effects of antihypertensive drugs such as amlodipine and captopril. The results showed a significant increase in participants’ knowledge scores, with the average pre-test score of 72.33 rising to 81.33 in the post-test, indicating improved understanding of medication use. Interactive discussions and leaflets were effective in enhancing awareness of the importance of therapy adherence and the risks of medication misuse. These findings support the need for continuous education programs to reduce the risk of hypertension complications in the community and to optimize antihypertensive medication management at the community level.